Avaliação psicológica no domínio das toxicodependências: das estruturas aos processos - Celina Manita (2002)
After a short reference to the historical evolution of last decades evaluation orienting paradigms and to the relationship between psychological evaluation, psychodiagnosis and intervention with drug addicts, some existing instruments of evaluation ("general" and "specific" to drug addiction situations) are presented. We discuss the need for an evaluation that goes further the structures and evaluates procedures and meanings, the demands of psychological evaluation and the absence of evaluation instruments constructed or adapted to our country, as well as the reduced number of specific instruments of evaluation for the field of drug addiction. Among all the mentioned instruments, Rorschach Test is particularly deepened.